2022
DOI: 10.1186/s43055-022-00895-w
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration cytology versus core needle lymph node biopsy in axillary staging of breast cancer

Abstract: Background Axillary lymph node status is an extremely important prognostic factor in evaluating and managing recently diagnosed breast cancer patients. So, preoperative evaluation of the lymph nodes in breast cancer patients with minimally invasive methods is of significant concern. Ultrasonography is the main modality used for this purpose, with advantages including the ability to help to guide the biopsy. This study aimed to compare ultrasound-guided fine-needle aspiration cytology (FNAC) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Mahmoud et al reported the principle on which the real-time USE is grounded that is under compression the harder or rigid parts of the tissues take more time in deforming as compared to the softer ones, which allows determining the maximum diameter of tissues with the help of conventional ultrasound showing indeterminate results. A 4-5 elasticity score of malignancy was highly predictive with an accuracy, specificity, and sensitivity of 90.20%, 89.47%, and 90.63%, respectively 24 .…”
Section: Discussionmentioning
confidence: 95%
“…Mahmoud et al reported the principle on which the real-time USE is grounded that is under compression the harder or rigid parts of the tissues take more time in deforming as compared to the softer ones, which allows determining the maximum diameter of tissues with the help of conventional ultrasound showing indeterminate results. A 4-5 elasticity score of malignancy was highly predictive with an accuracy, specificity, and sensitivity of 90.20%, 89.47%, and 90.63%, respectively 24 .…”
Section: Discussionmentioning
confidence: 95%
“…Different gold standards carry different diagnostic accuracies in determining LN malignancy. For example, studies have suggested that CNB has higher sensitivity than FNAC (87–100% and 74–83.3%, respectively), without significant differences in specificities (96–100% and 98–100%, respectively) [ 55 , 56 , 57 ]. When compared with surgical biopsy, CNB showed a lower sensitivity at 90% than its specificity at 100% due to false negative cases, and an LN biopsy is recommended in cases of suspected neoplasms [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…When compared with surgical biopsy, CNB showed a lower sensitivity at 90% than its specificity at 100% due to false negative cases, and an LN biopsy is recommended in cases of suspected neoplasms [ 58 , 59 ]. In malignancies such as lymphoma, CNB is often preferred over FNAC, mainly to preserve the tissue or nodal architecture to enable comprehensive histopathological review and diagnosis [ 55 , 56 , 57 ]. In head and neck squamous cell cancers, FNAC are deemed to be adequate in making a diagnosis in certain cases [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sonography can detect metastasis in ALNs based on the morphological characteristics of normal and suspicious LNs [14][15][16]. Furthermore, it is critical in guiding biopsies, such as ne-needle aspiration biopsy (FNAB) and/or core-needle biopsy (CNB), of suspicious lymph nodes to con rm the presence of metastases, which affects the management plans [17,18]. Numerous studies have been conducted in adjacent countries and around the world to evaluate the accuracy and use of sonography in diagnosing lymph node metastases, with sensitivity and speci city ranging from 55-95% [5,14,19].…”
Section: Introductionmentioning
confidence: 99%